Pembenahan Dan Pengembangan Perpustakaan Mini SD Negeri Jabung Wetan Sebagai Bentuk Kontribusi Mahasiswa Kampus Mengajar Angkatan 6 - Qurrotu Aini Nur Hidayah; Astri Widyaruli Anggraeni (Lembaga Pengembangan Kinerja Dosen, 2024)
Improving and developing the mini library at Jabung Wetan State Elementary School is a program designed by teaching campus students with the approval of the school and field supervisor lecturers (DPL). This program aims to meet the needs of the school community in the teaching and learning process, especially in increasing literacy activities for students' reading interest in the school environment. The method used in this service article is descriptive qualitative by going directly into the field to carry out observation and survey activities in school libraries.This program activity goes through several stages which include: (1) making and distributing book donation pamphlets to school residents and the outside community, (2) collecting donated books, (3) buying books from the money from donations, (4) cleaning and arranging the cooperative space which will be transformed into a library, (5) the process of decorating the library, (6) the process of classifying books based on their type, (7) writing a list of books into the main library book, (8) making labels for each books, (9) arranging and arranging books on shelves, (10) selecting and appointing library ambassadors.